2013
DOI: 10.1155/2013/979748
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Patterns in Brain Tumour Progression

Abstract: Inflammation represents the immune system response to external or internal aggressors such as injury or infection in certain tissues. The body's response to cancer has many parallels with inflammation and repair; the inflammatory cells and cytokines present in tumours are more likely to contribute to tumour growth, progression, and immunosuppression, rather than in building an effective antitumour defence. Using new proteomic technology, we have investigated serum profile of pro- (IL-1β, IL-6, IL-8, IL-12, GM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
117
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(126 citation statements)
references
References 46 publications
8
117
0
1
Order By: Relevance
“…Similarly, our results indicated that the IL-4 and IL-8 levels in serum were highly increased in patients with large cell lung carcinoma compared to non-cancer controls and to patients with adenocarcinoma as well as squamous cell lung carcinoma. Taken together, IL-1β, IL-4, IL-6 and IL-8 levels have been found to be elevated in most patients suffering from different common cancers [49,50]. Our results indicate that large cell lung carcinoma is associated with a systemic alteration in cytokines (IL-1β, IL-4, IL-6 and IL-8) and these cytokines have been shown to promote tumour growth and metastasis.…”
Section: Discussionsupporting
confidence: 52%
“…Similarly, our results indicated that the IL-4 and IL-8 levels in serum were highly increased in patients with large cell lung carcinoma compared to non-cancer controls and to patients with adenocarcinoma as well as squamous cell lung carcinoma. Taken together, IL-1β, IL-4, IL-6 and IL-8 levels have been found to be elevated in most patients suffering from different common cancers [49,50]. Our results indicate that large cell lung carcinoma is associated with a systemic alteration in cytokines (IL-1β, IL-4, IL-6 and IL-8) and these cytokines have been shown to promote tumour growth and metastasis.…”
Section: Discussionsupporting
confidence: 52%
“…Gliomas are ranked as the most aggressive brain tumors; they show a high frequency of invasion mediators such as angiogenic factors and chemokines (small-sized proteins, produced and released locally, intended for localized action) [1][2][3]. Simultaneous evaluation of multiple proteins in serum and cerebrospinal fluid allows for the identification of novel circulating biomarker panels helpful in disease diagnosis and treatment [4].…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous evaluation of multiple proteins in serum and cerebrospinal fluid allows for the identification of novel circulating biomarker panels helpful in disease diagnosis and treatment [4]. Therefore, in the last few years, proteomic approaches have been used to indicate potential cytokines, chemokines, and angiogenic factors for diagnosis and/or progression of primary brain tumors [1,5,6]. Using throughput xMAP technology, Albulescu et al identified serum profiles of cytokines and angiogenic factors (IL-6, IL-1β, IL-2, IL-10, TNF-α, VEGF, FGF-2, and GM-CSF) altered in glioblastoma patients [1].…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastoma is ranked as the most highly aggressive brain tumor which has high expression of mediators of invasion such as angiogenic factors and chemokines (Albulescu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%